Alpha-glutelin degradation and its hydrolysate by protease enhance the specific volume of gluten-free rice starch bread. (November 2021) - Honda, Yuji; Inoue, Nanami; Kurita, Moeka; Okunishi, Tomoya
Abstract: Protease has been shown to be an effective food additive for improving the quality of gluten-free rice bread. We found that rice protein hydrolysate by bacillolysin (Protin SD-NY10) and thermolysin (Thermoase) increased the specific volume of gluten-free rice starch bread. Many fine bubble cells were observed in the crumb of the rice starch bread containing rice protein hydrolysate by proteases using scanning electron microscopy. The temperature dependence between 30 and 60 °C of the tanδ values of the rice starch batter containing the protein hydrolysate was increased by comparing rice starch bread without the hydrolysate. SDS-PAGE of the rice protein hydrolysates by both proteases demonstrated that both proteases produced low molecular weight protein (ca 10 kDa) from α-glutelin in the rice protein. Judging from the protein hydrolysate by the proteases, the degradation of the α-glutelin and the hydrolysate are necessary to increase the specific volume of gluten-free rice starch bread. Graphical abstract: Image 1 Highlights: Rice protein is necessary to increase the specific volume of gluten-free rice bread. The protein hydrolysate enhanced the specific volume of gluten-free rice starch bread. Many fine cells in the crumb are important for an increase in the specific volume. Hydrolysate of α-glutelin enhances the specific volume of gluten-free rice bread.